Gastroparesis with Cannabis Use: A Retrospective Study from the Nationwide Inpatient Sample. Issue 7 (3rd October 2021) - Dahiya, Dushyant Singh; Kichloo, Asim; Shaka, Hafeez; Singh, Jagmeet; Edigin, Ehizogie; Solanki, Dhanshree; Eseaton, Precious Obehi; Wani, Farah
ABSTRACT: Background : With increasing utilization of cannabis in the United States (US), clinicians may encounter more cases of Gastroparesis (GP) in coming years. Objective : The primary outcome was inpatient mortality for GP with cannabis use. Secondary outcomes included system-based complications and the burden of the disease on the US healthcare system. Methods : From the Nationwide Inpatient Sample (NIS), we identified adult hospitalizations with a primary discharge diagnosis of GP for 2016 and 2017. Individuals ≤18 years of age were excluded. The study population was subdivided based on a secondary diagnosis of cannabis use. The outcomes included biodemographic characteristics, mortality, complications, and burden of disease on the US healthcare system. Results : For 2016 and 2017, we identified 99, 695 hospitalizations with GP. Of these hospitalizations, 8, 870 had a secondary diagnosis of cannabis use while 90, 825 served as controls. The prevalence of GP with cannabis use was 8.9%. For GP with cannabis use, the patients were younger (38.5 vs 48.1 years, p < 0.001) with a Black predominance (Table 1) and lower proportion of females (52.3 vs 68.3%, p < 0.001) compared to the non-cannabis use cohort. Additionally, the cannabis use cohort had higher percentage of patients with co-morbidities like hypertension, diabetes mellitus and a history of smoking. The inpatient mortality for GP with cannabis use was noted to be 0.27%. Furthermore, we noted shorter mean length of stay (LOS) (3.4 vs 4.4 days, aMD: −0.7, 95%CI: −0.9 – [−0.5], p < 0.001), lower mean total hospital charge (THC) (30, 400 vs 38, 100, aMD: −5100, 95%CI: −6900 – [−3200], p < 0.001), and lower rates of sepsis (0.11 vs 0.60%, aOR: 0.22, 95% CI: 0.05–0.91, p = 0.036) for GP hospitalizations with cannabis use compared to the non-cannabis use cohort. Conclusion : Inpatient mortality for GP hospitalizations with cannabis use was 0.27%. Additionally, these patients had shorter LOS, lower THC, and lower sepsis rates.